Correlations between skin hydration parameters and corneocyte‐derived parameters to characterize skin conditions. (30th March 2018) - Masaki, Hitoshi; Yamashita, Yuki; Kyotani, Daiki; Honda, Tatsuya; Takano, Kenichi; Tamura, Toshiyasu; Mizutani, Taeko; Okano, Yuri
Summary: Background: Skin hydration is generally assessed using the parameters of skin surface water content (SWC) and trans‐epidermal water loss (TEWL). To date, few studies have characterized skin conditions using correlations between skin hydration parameters and corneocyte parameters. Aims: The parameters SWC and TEWL allow the classification of skin conditions into four distinct Groups. The purpose of this study was to assess the characteristics of skin conditions classified by SWC and TEWL for correlations with parameters from corneocytes. Methods: A human volunteer test was conducted that measured SWC and TEWL. As corneocyte‐derived parameters, the size and thick abrasion ratios, the ratio of sulfhydryl groups and disulfide bonds (SH/SS) and CP levels were analyzed. Results: Volunteers were classified by their median SWC and TEWL values into 4 Groups: Group I (high SWC/low TEWL), Group II (high SWC/high TEWL), Group III (low SWC/low TEWL), and Group IV (low SWC/high TEWL). Group IV showed a significantly smaller size of corneocytes. Groups III and IV had significantly higher thick abrasion ratios and CP levels. Group I had a significantly lower SH/SS value. The SWC/TEWL value showed a decline in order from Group I to Group IV. Conclusion: Groups classified by their SWC and TEWL values showed characteristic skin conditions. We propose that the SWC and TEWL ratio is a comprehensive parameter to assess skin conditions.